Addressing Interpersonal Violence as a Health Policy Question Using Interprofessional Community Educators - Amy Clithero; Danielle Albright; Elena Bissell; Gabe Campos; Karen Armitage; Brian Solan; Cameron Crandall (Association of American Medical Colleges, 2016)
Abstract Introduction The health effects of intimate partner violence (IPV) not only include physical injury, but can also manifest as posttraumatic stress disorder, anxiety, and others. US medical students report receiving inadequate training about IPV. This case-based tutorial for third-year medical students examines: (1) a clinical encounter with a patient experiencing several complex challenges including IPV and homelessness; (2) the implications of existing policy on the delivery of health care services; and (3) the impact of policies on patient choices. Methods This case is completed during a family medicine clerkship. The 2-hour case review moves between small- and large-group sessions led by community interprofessional experts at a local family advocacy center. Optimal group size is three to four students and one or two experts per group. The large-group session should be led by a dynamic moderator who is familiar with the Socratic method of teaching to elicit a variety of responses to ad hoc challenge questions. Materials provided include student resources, student case, facilitator guide, moderator guide, and sample brochure of IPV documentation policies. Results To date, over 200 students have participated in this session. During the most recent iteration the average response to the question, "As a result of the FAC experience, I feel more empowered to care for persons experiencing IPV," was 4.1 out of 5 (5 = strongly agree). Discussion Public health, health policy, and clinical topics can be effectively taught by an interprofessional team of community experts and lead to improved student understanding of the importance of health policy to both individual and population health outcomes.